NIPAH virus encephalitis: Unveiling the epidemiology, risk factors, and clinical outcomes - A systematic review and meta-analysis - Neelam Suman; Ekta Khandelwal; Pavankumar Chiluvuri; Diptesh S Rami; Shivakshi Chansoria; Aldrin Jerry; Rahul Tiwari (Wolters Kluwer Medknow Publications, 2024)
Objective: This study assessed Nipah virus (NiV) encephalitis epidemiology, clinical outcomes, and risk variables to inform treatment and prevention. Methodology: In a PubMed systematic search, 929 citations were found. After screening and eligibility, 22 studies were included. This study obtained age, gender, geographic regions, diagnostic methods, data collection methods, and bias risk. The case fatality rate (CFR) and NiV infection risk variables were evaluated by meta-analysis. Results: Southeast Asia, especially Bangladesh and Malaysia, had the most NiV cases. The major diagnostic method was blood and cerebrospinal fluid IgM and IgG antibody tests, and males predominated. Proxy respondents and matched controls were utilized for risk factor analyses when patients could not answer. The pooled CFR for NiV encephalitis was 61.0%, indicating severity. Risk factors included pigs, nighttime bats near homes, tree climbing, and male gender. Conclusion: Southeast Asian public health is plagued by NiV encephalitis. The high CFR calls for better diagnosis, treatment, and prevention. NiV's multiple risk factors must be understood for targeted therapy. Future research should fill knowledge gaps and improve NiV infection prevention.